2008
DOI: 10.1177/1087054707305111
|View full text |Cite
|
Sign up to set email alerts
|

Discordance Between Psychometric Testing and Questionnaire-Based Definitions of Executive Function Deficits in Individuals With ADHD

Abstract: Results indicate that behavioral questionnaires cannot be used interchangeably with neuropsychological testing for the assessment of EFDs in adults with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 13 publications
(18 reference statements)
7
97
1
3
Order By: Relevance
“…The study by Oades et al found that there were trends for separate and overlapping influences on impulsive-aggressive behavior and cognitive impulsivity [Oades et al, 2008]. We also note that some evidence suggests that there is little shared variance between neuropsychological measures of executive dysfunction (such as the Stroop) and behavioral measures (such as the BRIEF) [Biederman et al, 2008b]. Since we only found the association between MAOA with the inhibition function evaluated by the BRIEF scale but not the Stroop test, it will compel us to consider that the association between MAOA with inhibition function may exist in some other dimensions but not that demonstrated by the Stroop test we have used.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The study by Oades et al found that there were trends for separate and overlapping influences on impulsive-aggressive behavior and cognitive impulsivity [Oades et al, 2008]. We also note that some evidence suggests that there is little shared variance between neuropsychological measures of executive dysfunction (such as the Stroop) and behavioral measures (such as the BRIEF) [Biederman et al, 2008b]. Since we only found the association between MAOA with the inhibition function evaluated by the BRIEF scale but not the Stroop test, it will compel us to consider that the association between MAOA with inhibition function may exist in some other dimensions but not that demonstrated by the Stroop test we have used.…”
Section: Discussionsupporting
confidence: 48%
“…The study by Rommelse indicated that the same ATT haplotype comprised of rs12843268, rs3027400, and rs1137070 was associated with poorer motor control in boys (P ¼ 0.002), but with better visuo-spatial working memory in girls (P ¼ 0.01) [Rommelse et al, 2008a]. Another study also suggested the gender effect of COMT, SLC6A4, SLC6A2, and MAOA for ADHD [Biederman et al, 2008b]. Our gender-specific analyses showed the association between rs3788862 with male ADHD and the same single SNP and haplotypic associations in males with ADHD-HI as were seen in the entire ADHD-HI sample in family-based association test, while none of these associations were found for females.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a large randomized placebocontrolled clinical trial of OROS-MPH in adults with ADHD found that ADHD participants continued to have a large burden of impairing self-reported EFDs, despite robust improvements in ADHD symptoms [33]. Our group also used data from a longitudinal naturalistic study of ADHD children treated in their communities with stimulants and reported that stimulants had limited effect on self-reported measures EFDs [34]. Finally, the limited effects of OROS-MPH on WM are consistent with clinical observations of continued problems with academic and work performance in individuals with ADHD despite well-controlled ADHD symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…Findings have not indicated concordance between the parent ratings on the BRIEF and direct measures in children with ADHD (Jonsdottir et al 2006;Sullivan and Riccio 2007), traumatic brain injury (Vriezen and Pigott 2002), ADHD (Biederman et al 2008), brain diseases such as phenylketonuria, hydrocephalus, or frontal focal lesions (Anderson et al 2002). These findings indicate that behavioral questionnaires may not evaluate the same skills as measured by direct tests of EF but may reflect the child's performance in various environmental contexts.…”
Section: Ef Behavior Rating Scalesmentioning
confidence: 93%